PENGARUH KUALITAS GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING - Novida Dwi Khumairoh; Yudhanta Sambharakreshna; Nurul Kompyurini (Master of Accounting Universitas Trunojoyo Madura, 2014)
The purposes of this research are to know some empirical evidence about influence of quality of Good Corporate Governance on firm value with financial performance as intervening variables, and effectiveness of Good Corporate Governance influence either directly or indirectly to the firm falue. Analysis method that used in this research is path analytical method with pooled data approach. Sample of this research is company successively participated in ranking of CGPI in 2009-2012. The sampling method that used is purposive sampling with total sample of 10 companies.The quality of GCG has not influence to ROA, and significantly positive influence to ROE and NPM. ROA variable has significantly positive influence to Tobin’s Q, but ROE and NPM have not significantly negative influence on Tobin’s Q. The quality of GCG has not significantly negative influence to Tobin’s Q directly. for indirect influence indicates that NPM, ROA and ROE are unprovable as intervening variable